The Effect Of Motivation And Job Satisfaction On Nurse Performance At The Pamulang Baby Mother And Child Hospital (RSIA) - Hanafi, Hanafi; Madiistriyatno, Harries; Panjaitan, Eddy H.H. (Jurnal Ekonomi, 2024)
The author's aim in this research is to find out how much influence motivation and job satisfaction have on improving nurse performance both partially and simultaneously at the Buah Hati Pamulang Mother and Child Hospital (RSIA) . The method used in this research is a quantitative research method with descriptive and verification methods. The sampling technique used in this research was the Slovin formula, and the data analysis technique used was a linear regression analysis technique using the SPSS version 25.0 application. Based on the analysis carried out, it can be concluded that motivation and job satisfaction can significantly influence Performance of Nurses at the Pamulang Mother and Child Hospital (RSIA). Based on respondents' perceptions, work motivation and job satisfaction are in the good category. Likewise, the performance variable is included in the good category . Partially, there are strong and significant implications of work motivation in improving performance, as well as providing job satisfaction large and significant influence on performance. Taken together, there is a large and significant influence of motivation and job satisfaction on the performance of nurses at the Buah Hati Pamulang Mother and Child Hospital (RSIA).